(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article aims to provide an overview of pneumonia in children, its causes, symptoms, prevention strategies and treatments. Pneumonia is an important respiratory infection that affects millions of children worldwide and causes significant morbidity and mortality. By understanding the different aspects of pneumonia, proactive measures can be taken to reduce its impact on children’s health.